Tashkent Medical Academy Termiz Branch Microbiology, public department of health hygiene and management, assistant of microbiology, virology, immunology (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Biological-hygienic aspects of the impact of soil composition on public health in the southern border regions. Abstract: In the southern regions, the soil composition remains mostly saline, and the state of usability is common. It is precisely in the desert regions that productivity is low, which has a great impact on the health of the population and causes a lot of dust storms.